Faktor yang Mempengaruhi Kinerja Keuangan Perbankan Syariah, Termasuk Kualitas Audit Syariah, Dewan Direksi dan Pengawas, Independensi Auditor, Good Corporate Governance (GCG), Serta Kepatuhan Syariah : Studi Literatur Review - Aghry Ghoriyyudin; Harry Z. Soeratin (Jurnal Ekonomi Manajemen Akuntansi, 2024)
Pay close attention to financial performance. An organization's success is shown by its consistent improvement in financial performance compared to the prior period. Audit quality, independence of auditors, Good Corporate Governance (GCG) implementation, regulatory compliance, and the organization's board of directors and supervisory board all have an impact on financial performance. The objective of this research is to corroborate and analyze prior studies that have focused on Islamic audit quality, Islamic audit independence, Islamic audit boards and supervisory boards, sharia compliance, good corporate governance (gcg), and auditor independence as they pertain to Islamic banking's financial performance. Using data gathered from articles published in national journals to back up claims, this study integrates qualitative methodologies with a literature review approach. The researcher procured ten samples of sinta indexed and non-indexed publications from Google Scholar. The study's findings suggest that financial performance is influenced by factors such as the quality of sharia audits, the independence of auditors, the degree of sharia compliance, the application of good corporate governance (gcg), and the board of directors and supervisory board. The researcher is optimistic that future studies will investigate the elements impacting financial success in more depth.